Study of Positioning Accuracy Parameters in Selected Configurations of a Modular Industrial Robot—Part 1 - Marcin Suszyński; Marcin Wiśniewski; Kajetan Wojciechowicz; Marek Trączyński; Marcin Butlewski; Vit Cernohlavek; Rafał Talar (Sensors)
This article presents the fundamental principles of robot accuracy. It characterizes a modular robot, describes the measurement setup, and outlines the methodology for evaluating positioning accuracy across different configurations of the modular robot (four, five, and six modules) under varying loads of 6, 10, and 16 kg. An analysis was conducted on the impact of load changes on four- and five-module configurations, as well as the effect of configuration changes on the robot’s performance with 6 and 10 kg loads. The findings indicate that both the number of modules and the load affect positioning accuracy. This article highlights the importance of selecting the optimal configuration based on planned industrial tasks to ensure the highest precision and operational efficiency.